IJCM_56A: What determines decision making among women? Insights from National Family Health Survey-5 - Madan Isha; Pracheth R; Bas Parama (Wolters Kluwer Medknow Publications, 2024)
Background: Women's empowerment is a critical driver for economic growth and social prosperity. Broadly, the term refers to an improvement in women's political, social, educational, economic, and health status. Decision making is an integral component of women's empowerment. Objective: This secondary data analysis from NFHS 5 aims to measure the level of women decision-making capability and its determinants among women aged 15-49 years in India. Methodology: We have analyzed the latest available data from the National Family Health Survey-5 (NFHS-5) gathered from the Demographic Health Survey program after obtaining permission. Descriptive statistics were applied to determine the decision making among women. Logistic regression was applied to compute adjusted odds ratio (AOR) for determining the associated factors of women decision-making capability and p-values < 0.05 were considered statistically significant. Results: The total women respondents in the NFHS 5 dataset were 721145, of which data regarding women decision making was available for 77729 (10.7%). Total 68942(88.7%) women were involved in decision-making. Decision-making capacity was found to be significantly associated with age, education level, working status. Women aged more than 30 years were found to have more involvement in decision making as compared to those aged less than 30 years (AOR=1.76; CI=1.684-1.842; p< 0.05). Decision making was significantly associated with education (AOR=0.847; CI=0.807-0.889; p< 0.05). Working women were involved more in decision making as compared to non-working (AOR=1.494; CI=1.414-1.578; p< 0.05). Conclusion: This study sheds light on the relationship between women decision-making capacity and its association with sociodemographic variables. Several factors were found to be significantly associated with women decision making capability.